2021
DOI: 10.5812/archcid.90861
|View full text |Cite
|
Sign up to set email alerts
|

Possible Association and Risk Factors of Blastocystis Infection and Colorectal Cancers in Western Iran

Abstract: Background: Recently, infection has been considered one of the most important causes of cancers because a large number of cases of cancer with infectious origin was reported. Objectives: The present investigation aimed to evaluate the prevalence and risk factors of Blastocystis hominis infection in patients with colorectal cancer in comparison to healthy individuals. Methods: The present descriptive case-control study was performed on 67 healthy individuals and 67 patients with colorectal cancers attending the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(30 reference statements)
2
2
0
Order By: Relevance
“…We have detected more Blastocystis infection in males (36.4%) compared to females (23.3%), in agreement with previous studies which have reported that Blastocystis was higher in males (11.8-53.8%) versus females (0-46.2%) ( 2 , 44 , 45 , 47 , 53 ). Ali et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We have detected more Blastocystis infection in males (36.4%) compared to females (23.3%), in agreement with previous studies which have reported that Blastocystis was higher in males (11.8-53.8%) versus females (0-46.2%) ( 2 , 44 , 45 , 47 , 53 ). Ali et al.…”
Section: Discussionsupporting
confidence: 92%
“…Generally, Blastocystis infections were detected consistently in patients receiving ≥8 chemotherapy cycles compared to earlier cycles, and compared to patients who did not start treatment ( 47 , 53 , 54 ). Interestingly, current study findings and previous studies suggest that CRC patients had a significantly higher Blastocystis prevalence than healthy participants, regardless of their treatment status ( 43 , 45 , 46 ). Also, COGT patients receiving multiple chemotherapy cycles presented a significantly higher Blastocystis infection than healthy participants ( 43 , 50 ).…”
Section: Discussionsupporting
confidence: 57%
“…Whereas, colorectal, stomach, esophagus and non-gastrointestinal cancer such as lung, liver, breast, ovarian, hematologic and other cancers were detected in adults. Among the 10 studies focused on cancer patients, six studies clearly stated that cancer patients were receiving chemotherapy treatment [82][83][84][85]87,88]. One study recruited cancer patients who have not received any chemotherapy [89].…”
Section: Blastocystis Spp Infection In Humansmentioning
confidence: 99%
“…Among various types, breast cancer is the most prevalent and the second most deadly type of cancer. Mostly, females of 45 to 55 years of age are affected by it [5][6][7][8][9][10][11]. The transmembrane tyrosine kinase receptor family is termed the human epidermal growth factor receptor (HER family), which is comprised of four types of proteins (HER1-HER4) [12].…”
Section: Introductionmentioning
confidence: 99%